(2) بحث التخطيط طويل الأجل مجموعة المؤشرات الإحصائية الأرقام القياسية (مسلسل2 ) Research on long-term planning: Statistical indicators set, index numbers (Series 2) - نادية مكاري (معهد التخطيط القومي, 2026)
يتناول هذا البحث الصادر عن معهد التخطيط القومي عام 1967 مفهوم الأرقام القياسية كأداة إحصائية أساسية لقياس وتتبع التغيرات في الظواهر الاقتصادية والاجتماعية عبر الزمن أو المكان، مثل الأسعار والكميات. ويستعرض البحث التطور التاريخي لهذه الأرقام منذ القرن الثامن عشر، مبيناً الطرق المختلفة لتركيبها سواء كانت بسيطة أو مرجحة (مثل أرقام لاسبير، وباش، وفيشر)، مع التركيز على المعايير النظرية والتطبيقية للمفاضلة بين هذه الصيغ لضمان دقة النتائج في التعبير عن الواقع الاقتصادي. كما يسلط الضوء بشكل مفصل على واقع الأرقام القياسية في الجمهورية العربية المتحدة آنذاك، مستعرضاً أنواعاً حيوية منها كالرقم القياسي لأسعار المستهلكين (نفقة المعيشة)، والأرقام القياسية للإنتاج الصناعي، والأجور، وأسعار الجملة، والتجارة الخارجية. ويناقش البحث التحديات العملية التي تواجه عملية إعداد هذه المؤشرات، مثل اختيار فترة الأساس المناسبة وتحديد الأوزان الترجيحية، مع الإشارة إلى الجهود التي بذلها الجهاز المركزي للتعبئة العامة والإحصاء لتطوير هذه الأدوات وتحديث بياناتها لتصبح مؤشراً حقيقياً يساعد في تحليل الأوضاع وإجراء البحوث الاقتصادية والتخطيط طويل الأجل. This research, published by the National Planning Institute in 1967, examines the concept of price indices as a fundamental statistical tool for measuring and tracking changes in economic and social phenomena across time and space, such as prices and quantities. The research reviews the historical development of these indices since the 18th century, outlining the various methods of constructing them, whether simple or weighted (such as Laspeyres, Pasch, and Fisher indices), while focusing on the theoretical and applied criteria for choosing between these formulas to ensure the accuracy of the results in reflecting economic reality. It also sheds light in detail on the state of price indices in the United Arab Republic at that time, reviewing key types such as the Consumer Price Index (CPI), industrial production indices, wages, wholesale prices, and foreign trade indices. The research discusses the practical challenges facing the preparation of these indices, such as selecting an appropriate base period and determining weighting criteria, while also acknowledging the efforts made by the Central Agency for Public Mobilization and Statistics to develop these tools and update their data to become reliable indicators that aid in analyzing conditions, conducting economic research, and long-term planning.